2014
DOI: 10.1016/j.seizure.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of the head-up tilt test in patients with suspected epilepsy

Abstract: NCS is an important cause of epilepsy misdiagnosis. The HUTT is often critical for making an accurate diagnosis and subsequently selecting the appropriate treatment for patients presenting with TLOC. The diagnostic overlap between epilepsy and NCS is not uncommon, suggesting that electroencephalographic monitoring during a HUTT may play an important role in diagnosing patients with recurrent, undiagnosed TLOC episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Four were population-based [9,10,24,32] studies recruiting patients from a base population of 75,200 [32], 15,000 [24], 200,000 [9] and 40,000 [10], respectively. Five studies (nine reports [21][22][23]27,[33][34][35][36][37]) recruited patients from head up tilt test (HUTT) or implantable electrocardiogram (ECG) recorder (ILR) centres. The remaining 17 studies recruited patients from epilepsy centres or tertiary hospitals.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four were population-based [9,10,24,32] studies recruiting patients from a base population of 75,200 [32], 15,000 [24], 200,000 [9] and 40,000 [10], respectively. Five studies (nine reports [21][22][23]27,[33][34][35][36][37]) recruited patients from head up tilt test (HUTT) or implantable electrocardiogram (ECG) recorder (ILR) centres. The remaining 17 studies recruited patients from epilepsy centres or tertiary hospitals.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The remaining 17 studies recruited patients from epilepsy centres or tertiary hospitals. One study [25] recruited patients with pseudo-refractory epilepsy, five studies (seven reports [34][35][36][38][39][40][41]) recruited patients with refractory epilepsy.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…More importantly, it is possible that VVS and epilepsy coexist. Recent study indicated that 21 percent of epilepsy patients demonstrated the positive head-up tilt table test 17. Thus, even patients compatible to the criteria of syncope used in this study, still have a possibility that their unconsciousness resulted from seizure.…”
Section: Discussionmentioning
confidence: 56%
“…Few studies addressed the overlap between syncope and epilepsy [ 1 , 17 , 18 ]. Although the selection of patients was very restrictive (2.2% of consecutive patients followed in the Epilepsy Centers) OESYS shows a very high occurrence of syncope, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This could implicitly confirm the presence of epilepsy in this group, in some cases, coexisting with syncope. Rangel et al showed the coexistence of syncope and epilepsy only in 21% of the patients with refractory epilepsy [ 18 ]. As suggested before, the higher prevalence observed in our study may be due to a higher mean age with respect to those patients studied by Rangel et al [ 18 ].…”
Section: Discussionmentioning
confidence: 99%